Optimizing low impact development (LID) practices in subtropical climate - Macedo, Marina Batalini de (2017)
The urban drainage in Brazil has been focused historically in the hydraulic conduction of the runoff. From the 1990\'s a paradigm shift was initiated with the study of LID practices, aiming at adapting the local scenario to compensate the urbanization effects on runoff and reestablish the water cycle as close as possible to the natural. However, there is still a gap regarding the integration of qualitative-quantitative variables and their comprehension. In addition, the temperate climate regions have been in the center of the studies, with still few knowledge about other climates influence in its efficiency. Therefore, this research aimed to evaluate the operation of a bioretention structure in a subtropical climate region, regarding mainly its pollutant treatment capacity and water retention, in an integrated way. The results indicate a positive use of the bioretention in reducing the exceedance risks, by reducing the peak flow, the total volume and the pollutant load transferred downstream. However, adaptations the implementation and operation stages are necessary for subtropical climates. The local specific characteristics, such as soil highly weathered and rainfall with high intensities in short intervals of time, affect the water and pollutant retention efficiency. Further studies evaluating different applications locals and scales, and treatment key factors must be performed.